Growth, Immunity, and Transcriptome Response to Dietary Wnt/β-Catenin Pathway Activator TWS119 in Penaeus vannamei - Hou, Cuihong; Song, Shougang; Zhu, Lulu; Shi, Lili; Tan, Beiping; Zhang, Shuang (Frontiers in Marine Science, 2021)
Wnt/β-catenin signaling has been proved to play an important role in the immunity of Litopenaeus vannamei. In this study, the effect of dietary Wnt/β-catenin pathway activator TWS119 on the growth, the immunity and transcriptome response in L. vannamei were investigated. L. vannamei were fed by diets added with TWS119 at the dose of 0 (T0), 0.25 (T0.25), 1 (T1), 4 (T4), 16 (T16), or 64 mg·kg−1 (T64), respectively. LvGSK3β activity were effectively inhibited in the L. vannamei fed by TWS119. The growth of L. vannamei in T16 group were significantly improved when compared with the control group. After Vibrio parahaemolyticus infection, the survival rates of L. vannamei in all the experimental groups but not T64 group were significantly higher than that in T0 group. Compared with the control group, the activities of the immune enzymes in the serum of L. vannamei increased in all the experimental groups, while the MDA contents decreased. Transcriptome analysis identified 5073 differentially expressed genes (DEGs) between L.vannamei in T0 and T16 groups. Most of the DEGs involved in the ribosome pathway, the endocytosis, glycerophospholipid metabolism, Wnt signaling pathway and FoxO signaling pathway. The ribosome pathway possessed the largest number of DEGs and was also the most significantly enriched pathway. The study indicated that growth and immunity of L. vannamei could be improved by dietary TWS119, which probably play a role through regulating the activity of Wnt/β-catenin pathway, and it may be closely related to the function of ribosome and energy metabolism.